A Review on Puerulus (Panulirus spp.) Resource Utilization in Indonesia Based on the Sense of Hearing: Auditory Receptor Organs - Hari Subagio; Evron Asrial; Yusnaini Yusnaini; Nurul Rosana; Gatut Bintoro; Nuhman Nuhman; I Made Kawan (Jurnal Ilmiah Perikanan dan Kelautan)
Highlight Research • The mortality of lobster seeds by predators in the first year is 96.0-99.4% • It takes technology to catch seeds before being eaten by predators • Application of sound wave-based attractor technology to lobsters • Do lobsters have the ability to hear sound waves? • The lobster's sense of hearing begins to function from the puerulus stage